Inhibition of the Notch1 Pathway Promotes the Effects of Nucleus Pulposus Cell-Derived Exosomes on the Differentiation of Mesenchymal Stem Cells into Nucleus Pulposus-Like Cells in Rats. (6th May 2019) - Lan, Wei-ren; Pan, Sai; Li, Hai-yin; Sun, Chao; Chang, Xian; Lu, Kang; Jiang, Chang-qing; Zuo, Rui; Zhou, Yue; Li, Chang-qing
Abstract : Stem cell therapies for intervertebral disc degeneration have been demonstrated as a promising strategy. Previous studies have shown that human nucleus pulposus cell- (NPC-) derived exosomes can induce the differentiation of mesenchymal stem cells (MSCs) into NP-like cells in vitro. However, the mechanism of MSC differentiation into NP-like cells with the induction of NPC exosomes is still unclear. Here, we verified the induction effects of NPC exosomes on the differentiation of MSCs into NP-like cells. In addition, the Notch1 pathway was downregulated in this process. Then, DAPT and soluble Jagged1 (SJAG) were applied to inhibit or enhance the expression of the Notch1 pathway, respectively, resulting in the upregulation or downregulation of collagen II, aggrecan, and Sox9 in MSCs. Knocking down of Notch1 protein facilitated the effects of NPC exosomes on the differentiation of MSCs into NP-like cells. NPC exosomes were more effective than an indirect coculture system in terms of the differentiation of MSCs into NP-like cells. Inhibition of NPC exosome secretion with Rab27a siRNA prevented the induction effects of an indirect coculture system on the differentiation of MSCs into NP-like cells. Transwell migration assays revealed that NPC exosomes could promote the migration of MSCs. Taken together, the Notch1 pathway was negatively associated with the differentiation of MSCs into NP-like cells with the treatments of NPC exosomes. Inhibition of the Notch1 pathway facilitates NPC exosome-induced differentiation of MSCs into NP-like cells in vitro. NPC exosomes play a key role in the differentiation of MSCs into NP-like cells in an indirect coculture system of NPCs and MSCs.